2008
DOI: 10.1124/dmd.108.021659
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Urinary Metabolites of Berberine in Rats and Humans

Abstract: ABSTRACT:The urinary metabolites of berberine, an isoquinoline alkaloid isolated from several Chinese herbal medicines, were investigated in rats and humans. Using macroporous adsorption resin chromatography, open octadecyl silane column chromatography and preparative high-performance liquid chromatography, we isolated seven metabolites (HM1-HM7) from human urine and five metabolites (RM1-RM5) from rat urine after oral administration. Berberine is an isoquinoline alkaloid isolated from several Chinese herbal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 26 publications
8
84
0
Order By: Relevance
“…Previous studies in vivo (Tsai and Tsai, 2004;Zuo et al, 2006;Qiu et al, 2008), including our more recent study in vitro (Liu et al, 2009), have well demonstrated that berberine is extensively metabolized in the body to generate M1 and M1 glucuronide via oxidative demethylation and subsequent glucuronidation and to form M2 and M2 glucuronide via oxidative demethylenation and subsequent glucuronidation. Therefore, UDP-glucuronosyltransferases have been identified as the major drug-metabolizing enzymes responsible for the formation of the phase II metabolites of berberine as shown by our more recent study in vitro (Liu et al, 2009) and this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in vivo (Tsai and Tsai, 2004;Zuo et al, 2006;Qiu et al, 2008), including our more recent study in vitro (Liu et al, 2009), have well demonstrated that berberine is extensively metabolized in the body to generate M1 and M1 glucuronide via oxidative demethylation and subsequent glucuronidation and to form M2 and M2 glucuronide via oxidative demethylenation and subsequent glucuronidation. Therefore, UDP-glucuronosyltransferases have been identified as the major drug-metabolizing enzymes responsible for the formation of the phase II metabolites of berberine as shown by our more recent study in vitro (Liu et al, 2009) and this study.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, an extremely low plasma concentration of berberine is associated mainly with the following PK causes: 1) extensive metabolism in the gut and/or liver (Tsai and Tsai, 2004;Zuo et al, 2006;Hao et al, 2007;Qiu et al, 2008); 2) marked excretion to intestinal lumen, bile (Tsai and Tsai, 2004), and urine (Qiu et al, 2008) (as a substrate of certain efflux transporters) (Xie, 2010), as well as enterohepatic circulation (Zuo et al, 2006;Xie, 2010); 3) poor absorption (due to some unique physicochemical properties); and 4) predominant tissue distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolites are very polar and easily excreted in urine. (41) A recent study has shown that orally administered berberine is detectable in the lung tissues of mice and inhibits in vivo tumorigenesis and growth of xenografted lung cell tumors. This indicates that viable concentrations of berberine are achievable through oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison with blank samples, full scanning in the m/z region of 50 to 700 allowed the assignment of several peaks to COP and its metabolites in the total ion chromatogram (TIC). Based on the drug metabolism rule and PBA (berberine, jatrorrhizine, and epiberberine) metabolite reports 15,16) (Table 4 and Fig. 6).…”
Section: In Vivo and In Vitro Identification Of Metabolitesmentioning
confidence: 99%